Pengaruh Komposisi Bahan Baku dan Ukuran Partikel Terhadap Kualitas Biobriket dari Cangkang Buah Karet dan Ranting Kayu - Iriany; Hasibuan, Rosdanelli; Novita, Dian; Ummah, Nisa’a Mufidatul (Talenta Publisher (Universitas Sumatera Utara), 2023)
Biobriquette is a solid fuel derived from raw materials that can be renewed continuously because it is made from a mixture of biomass such as wood, twigs, leaves, grass, straw and other agricultural wastes. The research aims to examine the effect of variations in the composition of raw materials and particle sizes were 50 mesh, 70 mesh, 100 mesh, and 120 mesh. This research was started by carrying out the pyrolysis process on the raw material with temperature 350 oC for sixty minutes, then the refined pyrolysis charcoal powder was mixed with starch adhesive 10% of the weight of the raw material which was then manually pressed cylindrical. The measurement results in this research were compared with quality parameters based on Indonesian National Standard (SNI), Japan, England, and America. The best result for this research is obtained at a ratio of rubber fruit shells and wood twigs 1:5 with a particle size of 100 mesh, that is with inherent moisture of 4.50%, ash content of 2.19%, volatile matter of 13.73%, density 2.2502 g/cm3, and caloric value 6,653.60 cal/g.